Design, theoretical approaches and new framework of pyrazolo[3,4-d]pyrimidine as potent anticancer agents: Efficient synthesis, ADME-T and molecular docking - Peduri Suresh Reddy; Thuraka Sekhar; Pinnu Thriveni; Gandla Mahesh Kumar; Allaka Tejeswara Rao; Mohammad Raish; Tota Giridhar; Gudipati Srinivasulu (Results in Chemistry)
Novel 1,3,4-thiadiazole-based pyrazolo[3,4-d]pyrimidine derivatives (7a–7 l) were synthesised in this study, and their structures were ascertained utilizing a range of spectroscopic methods, including HREI-MS, IR, and NMR (1H/13C). They showed especially strong activity (IC50 range 1.56–44 μM). With IC50 values of 2.49 ± 1.9, 1.56 ± 1.3, and 2.97 ± 2.6 μM against Caco-2, HCT116, and A549 cell lines, respectively, compound 7f demonstrated the strongest anticancer properties among all synthesised compounds when compared to the conventional medication doxorubicin (IC50 = 3.10 to 3.32 μM). Additionally, the anchoring function of the 1,3,4-thiadiazole-substituted pyrazolo[3,4-d]pyrimidine moiety in interacting with anticancer targets and hydrophobic interaction with the essential amino acid residues has been highlighted by molecular modeling studies. The study shows how certain residues from the colorectal cancer mutant (1WCH) interact with each other in a way that is stable. Furthermore, these compounds intriguing therapeutic potential is highlighted by their favorable drug-likeness and ADME-Tox characteristics, which call for more research into possible clinical applications. These compounds are attractive candidates for further investigation in the search for new therapeutic agents due to their diverse actions, which include anticancer qualities.